Holocene Thermokarst Lake Dynamics in Northern Interior Alaska: The Interplay of Climate, Fire, and Subsurface Hydrology - Anderson, Lesleigh; Edwards, Mary; Shapley, Mark D.; Finney, Bruce P.; Langdon, Catherine (Frontiers in Earth Science, 2019)
The current state of permafrost in Alaska, and meaningful expectations for its future evolution are better informed by long-term perspectives of previous permafrost degradation. Thermokarst processes in permafrost landscapes often leads to widespread lake formation. The spatial and temporal evolution of thermokarst lake landscapes reflects the combined effects of climate, ground conditions, vegetation, and fire. To further explore the Holocene history of Yukon Flats thermokarst lakes, we conducted a detailed study of Greenpepper lake, located on the southern loess uplands, including bathymetry and sediment core analyses across a water depth transect. The sediment results, dated by radiocarbon and 210Pb, indicate that Greenpepper basin development initiated ~8000 cal yr BP through inferred thermokarst processes. Thermokarst expansion to the modern lake’s near-shore shallow water depths continued to ~5000 and 4000 cal yr BP. Subsequently stable sediment chronologies and properties indicate the lake established levels ~4 m higher than present. At that time, water overflowed into an over-deepened gully system no longer occupied by perennial streams and connected to nearby partially drained lakes. By ~1000 cal yr BP, Greenpepper lake levels had lowered below the outflow elevation, which is interpreted to reflect a response to drier conditions and possibly to downgradient catastrophic lake drainage that increased subsurface water loss, although this mechanism is untested. Timing of Greenpepper thermokarst initiation and lake expansion was later than previously documented elsewhere in the southern loess upland and post-dates the establishment of spruce forest. After the lake stabilized by ~4 ka, the late Holocene millennial trend of increased aridity corresponds with Yukon Flats regional fire and paleoclimate reconstructions and suggest linkages with large scale Holocene patterns of North Pacific atmospheric circulation.